1968
DOI: 10.1111/j.0954-6820.1968.tb10432.x
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Some Ovulation Inhibitors on the Different Plasma Lipid Fractions

Abstract: A comparison has been made of the effects of three different combined oral contraceptives (Ovulen, Anovlar, and Volidan) on the plasma levels of cholesterol, triglycerides, and total and individual phospholipids. The results indicate a difference in action between Anovlar on the one hand and of Ovulen and Volidan on the other. In three oophorectomized women the effects of one of the estrogenic and two of the progestogenic components of the combined preparations were studied separately. The drugs were given sin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
2
0

Year Published

1969
1969
1979
1979

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(3 citation statements)
references
References 12 publications
1
2
0
Order By: Relevance
“…The results confirmed earlier studies which have shown increased plasma concentration of cholesterol and triglycerides (1,9,14,15,17,23) and decreased post-heparin lipolytic activity (1 5 ) during treatment with estrogen-containing oral contraceptives. Larsson-Cohn et al (17), employing the same agent as used in the present study, observed a decrease of plasma FFA.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The results confirmed earlier studies which have shown increased plasma concentration of cholesterol and triglycerides (1,9,14,15,17,23) and decreased post-heparin lipolytic activity (1 5 ) during treatment with estrogen-containing oral contraceptives. Larsson-Cohn et al (17), employing the same agent as used in the present study, observed a decrease of plasma FFA.…”
Section: Discussionsupporting
confidence: 91%
“…Oral contraceptive agents may raise the plasma triglyceride level (1,9,14,15,17,23). Hazzard et al (15) found that concomitantly with a raised concentration of plasma triglycerides there was a decrease of the post-heparin lipolytic activity and an increase of the basal plasma level of immunoreactive insulin, These authors discussed the possibility that the raised level of plasma triglycerides might be due to impaired removal from plasma related to the decrease in lipolytic activity.…”
mentioning
confidence: 99%
“…Further investigations in this direction may be indicated, as estrogens have a well-known lipidlowering effect (13,22). 7 he lysolecithin in plasma seems mainly io b: produced from lecithin via the acyl-transferase mechanism described by Glomset (1 6). Possibly also phospholipase A may be of importance (5).…”
Section: Discussionmentioning
confidence: 99%